Critical Residues in Hsp70 Nucleotide Binding Domain for Challenges in Drug Design - Ergul, Mustafa; Aktan, Fugen; Tutar, Yusuf (Current Proteomics, 2022)
Background: The association of a drug with its target protein correlates to its medicinal activity and the microenvironment plays a key role in this association. The key challenge is to identify mutations which unlikely to respond to designed drugs. Objective: Hsp70 is an anti-apoptotic factor and tumor cells overexpress Hsp70 to survive against anti-cancer agents. The impact of pathogenic mutations on Hsp70 is unknown. Elucidation of these alterations is essential to understand the molecular switch mechanism. Thus, critical spots on Hsp70 Nucleotide Binding Domain (NBD) are important since mutation-driven sensitivity may be useful in designing innovative inhibitors. Methods: ATP, AMP-PNP (non-hydrolyzable analog of ATP) along with commercially available compounds VER-155008 (ATP analog and competitive inhibitor) and MKT-077 (allosteric inhibitor of ADP bound form) were docked to Hsp70 NBD structure in silico to identify critical amino acids of inhibition mechanism. Site-directed mutagenesis of the determined critical residues along with ATP hydrolysis and luciferase refolding was performed. Wild-type and mutant Hsp70s were compared to determine the effect on protein functions in the presence or absence of inhibitors. Results: This study identified three mutants that have a loss of function for Hsp70, which may alter the drug inhibition activity as oncogenic cells have multiple mutations. Conclusion: Two commercial inhibitors employed here that mimic ATP and ADP states, respectively, are not affected by these mutational perturbations and displayed effective interference for Hsp70 functions. Designing inhibitors by considering these critical residues may improve drug design and increase drug efficiency.
Keywords: Nucleotide-binding domain